THE IMPACT OF ARTIFICIAL INTELLIGENCE (CHATGPT) ON PRODUCT AND SERVICE INNOVATION IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) AMONG GENERATION Z ENTREPRENEURS - Mochammad Rakha Abimanyu; Istian Kriya Almanfaluti; Bayu Hari Prasojo (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: This study aims to analyze the effect of ChatGPT utilization on product and service innovation in Micro, Small, and Medium Enterprises (MSMEs) managed by Generation Z in East Java. The purpose is to determine whether the application of artificial intelligence can significantly enhance the creativity, efficiency, and market relevance of MSME products and services. Method: The research employed a quantitative approach using a simple linear regression with the PLS-SEM method. A total of 99 respondents were selected through purposive sampling, focusing on Gen Z MSME owners who have used ChatGPT in their business activities. The data were analyzed using SmartPLS, which included measurement model testing (validity and reliability) and structural model testing (path coefficient, R², f², and significance). Results:  The findings indicate that ChatGPT usage has a positive and significant influence on product and service innovation, with a path coefficient value of 0.507, R² of 0.257, and f² of 0.346. These results demonstrate that although the explanatory power of the independent variable is statistically limited, the substantive effect is considered strong. This suggests that ChatGPT can support innovation processes by improving efficiency and enabling new ideas that align with market needs. Novelty: This research highlights the empirical evidence of how generative AI tools like ChatGPT can be directly linked to innovation outcomes among young entrepreneurs in Indonesia. The study contributes by emphasizing the role of AI adoption as a strategic driver of competitiveness for MSMEs in the digital era.